2009
DOI: 10.2172/962426
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Frit Development and Melt Rate Testing for Sludge Batch 6 (Sb6)

Abstract: DISCLAIMERThis work was prepared under an agreement with and funded by the U.S. Government. Neither the U. S. Government or its employees, nor any of its contractors, subcontractors or their employees, makes any express or implied: 1. warranty or assumes any legal liability for the accuracy, completeness, or for the use or results of such use of any information, product, or process disclosed; or 2. representation that such use or results of such use would not infringe privately owned rights; or 3. endorsement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…As previously mentioned, the results of the MRF have been used directly or in conjunction with SMRF testing to recommend frits and sludge preparation strategies to DWPF for sludge batches 1B through 6. 6,8,[14][15][16][17][18][19][20][21][22][23][24][25] In addition, these tools have allowed WL versus melting rate curves to be generated, which have been used to demonstrate where optimal waste throughput can be achieved for a given melter feed.…”
Section: Melting Rate Measurement Techniquementioning
confidence: 99%
“…As previously mentioned, the results of the MRF have been used directly or in conjunction with SMRF testing to recommend frits and sludge preparation strategies to DWPF for sludge batches 1B through 6. 6,8,[14][15][16][17][18][19][20][21][22][23][24][25] In addition, these tools have allowed WL versus melting rate curves to be generated, which have been used to demonstrate where optimal waste throughput can be achieved for a given melter feed.…”
Section: Melting Rate Measurement Techniquementioning
confidence: 99%
“…6 These tests showed that higher concentrations of B 2 O 3 in the frit relative to that of Frit 418 appeared to improve melt rate. However, when a higher concentration of B 2 O 3 was coupled with a lower concentration of Na 2 O relative to Frit 418, melt rate did not appear to improve.…”
Section: Introductionmentioning
confidence: 97%